Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Turnover Intetion Karyawan pada Pt. Telekomunikasi Indonesia (Telkom) Daerah Bima - Muhammad Tharfiq; Muhammad Yusuf; Kartin Aprianti (Institut Nalanda, 2024)
This research aims to determine the influence of workload and work environment on employee turnover intention. The sample used in this research was 50 respondents. Data collection techniques used observation, questionnaires and literature study. Data analysis technique using multiple linear regression. The results of the research show that partially and simultaneously workload and work environment do not have a significant effect on turnover intention among employees of PT Telekomunikasi Indonesia Bima Branch.